Understanding features and benefits: An analysis of ideational meaning in fashion, food & beverages and cosmetics advertisements - Fauzia Nurhaliza; Riesky Riesky; Ernie D A Imperiani (Universitas Pendidikan Indonesia (UPI), 2020)
In advertising, features and benefits are one of the most important elements for marketers to persuade their audience about products or services they sell. Drawing upon the features and benefits’ definition proposed by Bly (2005) and the transitivity theory proposed by Halliday Matthiessen (2004), this study focused on the way features and benefits are distributed and represented in fashion, food beverages, cosmetics advertisements. It analyzed three categories of most encountered advertisements on Instagram, incorporating features and benefits of the text in the caption box of Instagram advertisements. This study employed a descriptive qualitative method since it is credible to analyze this linguistic phenomenon and is useful to complement, validate, explain, or reinterpret the data in this study. In terms of distribution, this study found out that features are mostly discovered in Instagram advertisements rather than benefits, and features are used more by fashion and food beverages advertisements. Meanwhile, benefits are mostly encountered on cosmetics advertisements since cosmetics need to tell more about what the user of the product gains as a result of the features. Furthermore, in terms of transitivity analysis, it turns out that fashion and food beverages advertisements use more relational process on their texts, while cosmetics advertisements use more material process. These findings are quite predictable in this particular text type as the ads copywriter generally aims to arouse their potential customers’ interests, and this can be achieved by consistently describing product features as well as benefits.Keywords: Benefits, copywriting, features, Instagram ads, transitivity.